P116 Development of a new patient-reported outcome measure for patients with complex cryptoglandular fistulas. (27th May 2021) - McCurdy, J; Crooks, P; Gwaltney, C; Krupnick, R; Cadogan, K A; Gonzalez, S; Karki, C
Abstract: Background: Complex cryptoglandular fistulas (CCF) arise from infected anal glands and are often associated with substantial morbidity and healthcare utilization. Standarized patient-reported outcome measures (PROMs) for CCF are lacking. Thus, we aimed to develop a disease-specific PROM to assess the burden of symptoms and their impact on daily life in patients with CCF. Methods: To develop a conceptual model, a targeted literature review was conducted to identify symptoms and impacts on daily life associated with CCF. Existing PROMs relating to anal fistulas were also sought. Semi-structured interviews with colorectal surgeons (n=5) assessed clinical perspectives on patient experience of CCF. A draft item pool was developed based on the refined conceptual model and using the Quality of Life in Patients with Anal Fistula Questionnaire as a reference. The tool was refined through concept elicitation interviews on the symptoms and impacts of CCF, and cognitive debriefing on the interpretation, understanding and response to each item. Interviews were conducted until concept saturation was achieved and patient feedback suggested no further refinements were required. Results: The literature review identified discharge, pain, faecal incontinence and bleeding as the most prevalent symptoms, and embarrassment as the most prevalent impact on daily life. Results from surgeon interviews were then used to revise the initial conceptual model. Twenty US adults (60% female; mean age, 49 years) with clinically confirmed CCF participated in interviews (four waves of n=5). Patients identified 10 salient symptoms and 11 salient impacts on daily life (salient defined as mention by ≥50% of patients and mean disturbance rating ≥5 on a 10-point scale). The final conceptual model included the main symptoms and treatment-related effects, and impacts on daily life. The draft item pool was refined, resulting in a final PROM consisting of 14 items (covering frequency and severity) relating to symptom domains – discharge, incontinence, pain, irritation, odour, abscess – and 6 items relating to health-related quality of life domains – functional, physical, psychological, social health. The PROM features a 7-day recall period, with responses mostly given on a 5-point verbal rating scale. Cognitive debriefing confirmed that the PROM was clear, easy to understand and relevant to patients' experiences. Conclusion: The 20-item CCF questionnaire (CCFQ-20) is a new PROM that has been developed and tested for content validity, following expert guidance and regulatory best practices. It addresses a comprehensive set of salient symptoms and impacts experienced by patients with CCF. Psychometric testing is required to fully evaluate this PROM. Sponsor: Takeda Pharmaceuticals USA, Inc.